PERBEDAAN DAMPAK FATHERLESS PADA REMAJA PEREMPUAN DAN LAKI-LAKI: LITERATURE REVIEW - Ni Luh Komang Alit Suandari; David Hizkia Tobing (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The role of fathers is critical during adolescent development and growth. Fatherlessness affects adolescents' lives physically and psychologically. Differences in adolescent characteristics based on gender are likely to differentiate the impact of fatherlessness on female and male adolescents. This study examines the differences in the impact of fatherlessness on adolescents in terms of gender. The research was conducted by conducting a literature study. The literature search was conducted using the Google Scholar platform. Based on the results of the literature search, 376 journal results were found, but only 15 journals met the criteria and discussed the impact of fatherlessness on female and male adolescents with a publication range of 2020-2025. Based on the literature review, it was found that there are differences in the impact of fatherlessness on adolescent life in terms of gender. Female adolescents tend to experience obstacles in self-acceptance, interpersonal relationships, emotional intelligence, and anxiety. Meanwhile, the impact of fatherlessness on male adolescents tends to lead to aggressiveness, self-assessment, academic achievement, and self-concept. In addition, the role of significant others or parties involved in the lives of adolescents without a father figure has a huge influence on the success of these adolescents in the adaptation process.